MORPHOLOGICAL CHARACTERS AND YIELD OF ABACA AND RELATED MUSA CLONES IN BAYBAY, LEYTE, PHILIPPINES - Alcober, Enrique R. (Annals of Tropical Research, 1986)
Thirty-six clones of abaca and related Musa species were studied to determine their morphological characters, fiber yield and recovery, and tensile strength of their fibers; and to evaluate the relative merit of each parameter to fiber yield. The different clones showed wide variation in all the characters evaluated. Generally, clones with many suckers per hill produced more floating suckers. Basal and middle stalk circumference, length and weight of stalks, number of leaf sheaths per stalk, number of suckers and harvestable stalks per hill, and fiber recovery significantly influenced fiber yield.